Assessing Creative Writing: A Comparative Study Artificial Intelligence VS Human Mind. The Case of Master One EFL Students of English at the University of Souk-Ahras. - GUEDAIBIA Wissal (My University, 2024)
Abstract This study assesses writing creativity of Artificial Intelligence (AI) programs in comparison with the human mind in the context of writing short stories and essays. As the world witnesses a rapid advancement of AI technologies, particularly in natural language processing, there is a growing interest in understanding the extent to which these systems can replicate or even surpass human creativity in producing writing assignments such as short stories and essays. This study employs a mixed method, qualitative and quantitative; data are collected through a survey and a controlled experiment. The case of this study is Master One English as a Foreign Language (EFL) students at Mohamed Cherif Messaadia University. The participants are evenly divided into 10 experimental and 10 controlled groups. The findings reveal that ChatGPT demonstrates superior creativity in essay writing, while the human mind shines in crafting short stories. Additionally, the study provides a set of recommendations and suggestions for future investigations to advance our understanding of the relationship between AI and human creativity in writing -------------------- ملخص تهدف هذه الدراسة الى تقييم مدى ابداع برامج الذكاء االصطناعي بالمقارنة مع العقل البشري في سياق كتابة القصص القصيرة والمقاالت. مع التقدم السريع لتقنيات الذكاء االصطناعي الذي يشهده العالم، خاصة في اكتساب وتعلم اللغة بطريقة طبيعية، مما زاد في االهتمام لمحاولة فهم مدى قدرة هذه األنظمة على استنساخ او حتى تجاوز االبداع البشري في الكتابة اإلبداعية. لمقارنة ابداع العقل البشري مع الذكاء االصطناعي، تم استخدام طرق مختلفة، منها طريقة نوعية وأخرى كمية؛ حيث تم جمع البيانات من خالل استطالع وتجربة لطلبة اللغة اإلنجليزية كلغة أجنبية من السنة األولى ماستر بجامعة محمد الشريف مساعدية بسوق أهراس. تم تقسيم المشاركين بشكل متساو حيث ان 10 طالب استخدموا برنامج الشات جي بي تي و10 قاموا بالكتابة اعتمادا على مكتسباتهم المعرفية الشخصية. كشفت النتائج ان الشات جي بي تي كان أكثر ابداعا في كتابة المقاالت، بينما تألق العقل البشري في صياغة القصص القصيرة. اعتمادا على نتائج تقدم هذه الدراسة مجموعة من االقتراحات التي قد يتم العمل عليها كبحوث مستقبلية من اجل تعزيز فهمنا لعالقة الذكاء االصطناعي واالبداع البشري في الكتابة --------------------- Résumé Cette étude se penche sur l'évaluation de la créativité des programmes d'intelligence artificielle (IA) et de l'esprit humain dans le contexte de la rédaction de nouvelles et d'essais. Avec l'avancement rapide des technologies de l'IA, notamment dans le traitement du langage naturel, il y a un intérêt croissant à comprendre dans quelle mesure ces systèmes peuvent reproduire ou même surpasser la créativité humaine dans les tâches d'écriture créative. Cette étude utilise une méthode mixte, qualitative et quantitative ; les données sont collectées à travers une enquête et une expérience contrôlée. Le cas de cette étude concerne les étudiants de Master 1 en anglais langue étrangère (EFL) à l'Université Mohamed Cherif Messaadia. Les participants sont répartis de manière équitable en 10 groupes expérimentaux et 10 groupes témoins. Les résultats révèlent que ChatGPT démontre une créativité supérieure dans la rédaction d'essais, tandis que l'esprit humain brille dans la création de nouvelles. De plus, l'étude propose une série de recommandations et de suggestions accentuées pour de futures investigations afin de faire avancer notre compréhension de la relation entre l'IA et la créativité humaine dans l'écriture